Analysis of growth and nutritional quality of sea worms (Nereis virens) as a mass cultured natural feed on different substrate media thicknesses - Vivi Endar Herawati; Tita Elfitasari; Nurmanita Rismaningsih; Putut Har Riyadi; Woraporn Tarangkoon; Ocky Radjasa; Seto Windarto (Society for Indonesian Biodiversity, 2021)
Abstract. Herwati VE, Elfitasari T, Rismaningsih N, Riyadi PH, Tarangkoon W, Radjasa OK, Windarto S. 2021. Analysis of growth and nutritional quality of sea worms (Nereis virens) as a mass cultured natural feed on different substrate media thicknesses. Biodiversitas 22: 3299-3305. Sea worms (Nereis virens) grow slowly. The thickness of the substrate used in mass culture affects their growth, because N. virens is a deposit feeder that feeds on organic matter provided by other organisms; therefore, the growth rate slows down if the substrate thickness is not suitable. This study aimed to determine and analyze the growth and nutritional quality of N. virens as a natural feed in mass culture at different substrate media thicknesses. This study was conducted at the Marine Science Techno Park (MSTP) UNDIP, Jepara, Central Java. The test animals were two-month-old sea worms, weighing 0.15 to 0.5 g/individual. The maintenance media was the mangrove mud substrate. Feeding was carried out at a fixed feeding rate, twice a day at 07.00 and 19.00 hrs, and the animals were maintained at a density of 45 individuals/L for 35 days. The experimental research method was a completely randomized design with four treatments and three replications: treatment A (media thickness of 4 cm), B (media thickness of 6 cm), C (media thickness of 8 cm), and D (media thickness of 10 cm). The parameters studied were absolute growth, specific growth rate (SGR), efficiency of feed utilization (EFU), feed conversion ratio (FCR), protein efficiency ratio (PER), survival rate (SR), proximate analysis, profile of amino acid and fatty acids. The results showed that the highest absolute weight (6.76 g); SGR (6.34%); EFU (69.73%); FCR (1.36%); PER (1.74%); SR (97.04%); and nutritional quality (55.75% protein, 22.62% fat, 45.66 ppm methionine, and 7.7% eicosapentaenoic acid values were obtained when N. virens was mass-cultured in a medium with a thickness of 8 cm (Treatment C). Thus, the thickness of the media substrate had a significant effect (P < 0.05) on the absolute weight, SGR, EFU, FCR, PER, and SR in N. virens.